2019
DOI: 10.12707/riv18078
|View full text |Cite
|
Sign up to set email alerts
|

Noise in neonatology: perception of health professionals

Abstract: Background: The negative impact of noise in the newborn in neonatology units, as well as in the parents and health professionals, is known, so it is essential to raise awareness of the reduction and control of this stressor agent. Objectives: To identify the perception of health professionals about noise in neonatology. Methodology: Qualitative-quantitative and descriptive study. A non-probabilistic sample of 52 health professionals. An ad-hoc questionnaire designed for this purpose was used. Results: The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…These findings are concerning, as the recorded noise levels exceeded both Brazilian [8] and international recommendations [7] for hospitals. These results suggest that the NICU environment may potentially pose harm to both patients [34,35] and health professionals [36][37][38].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These findings are concerning, as the recorded noise levels exceeded both Brazilian [8] and international recommendations [7] for hospitals. These results suggest that the NICU environment may potentially pose harm to both patients [34,35] and health professionals [36][37][38].…”
Section: Discussionmentioning
confidence: 91%
“…In this study, noise was perceived as an "unpleasant" factor. The discomfort caused by noise in the work environment has negative impacts on professionals' performance [10,38,51]. It is crucial to raise professionals' awareness about their contribution to noise production when implementing strategies for noise control (Disher et al, 2017;Ahamed et al, 2018;Barsam, Barbosa, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This may adversely affect not only neonatal outcomes but also HCPs working in the NICU. Silva et al 26 conducted a survey of HCPs, including nurses, physicians, physiotherapists, and technical assistants, and reported that 77% of HCPs considered the NICU too noisy. Despite this perception, the results in our study show behaviors that seemed to demonstrate a lack of awareness of what they might be doing to decrease noise; for example, behaviors such as using a loud conventional voice at the bedside, failing to promptly silence alarms, and loudly opening and closing doors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite modern advances, the noise level within the incubator varies between 55 and 70 dB. contributing significantly to hearing insults despite theoretically providing partial protection from outside noise [38,44,52]. In addition, due to reverberance effects, the incubator amplifies the internal noise produced by the cooling fan as well as magnifies the intensity of the baby's cry.…”
Section: Noise-where Does It Come From?mentioning
confidence: 99%
“…In addition, incubators boost transmission of low frequencies (below 125 Hz) due to strong resonance [14]. Other incubator-associated activities such as closing doors generate a sound of 85 dB, placing an object on the incubator emits 90 dB, and closing the lower drawer of the incubator leads to an 89 dB level [38,44,49,52].…”
Section: Noise-where Does It Come From?mentioning
confidence: 99%